ADULT LITERACY: POTENTIAL STAGE FOR HEALTH PROMOTION - Rodríguez Villamil, Luz Natalia; Arias López, Beatriz Elena (Investigación y Educación en Enfermería, 2009)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Objective: to be able to understand the meaning of learning to read and write in everyday life situations for adults who live in slums of Medellín and the Aburrá valley in Antioquia, Colombia which take part on literacy processes focusing on pedagogy of the text. Methodology: qualitative investigation with a perspective of focused etnography, developed between July 2006 and July 2008, by means of group and individual interviews as well as observations of educational sessions and family environments. Thirty two adults participated, the majority of them mature and medium aged women. The analysis is based on the results of the program Atlas.ti. Results: while carrying out this educational experience the participants experience tensions derived from their inability to read and to have taken the decition to study at an advanced age. The meaning of the signature appeared as a symbolic element of identity, allowing the participation on spaces and public events. The strengthening of orality through reading and writing broadened the posibilities of social interaction. Conclusions: the intra and interpersonal identities are moved and transformed during the educational process. Those people until then blocked by the predominance of the written culture started a process of self recognition, changes on family relationships and a decrease on the feeling of uncertainty. Although this new knowledge begin to be embodied in their family and social life, they do not necessarily secure an improvement on life conditions. However a greater control and projection of the individual life plan is envisaged as recognized aspiration on the objectives of health promotion.